2005
DOI: 10.1007/s11661-005-0324-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography of the δ→α martensitic transformation in plutonium alloys

Abstract: A new stress-accommodating crystallographic mechanism of the martensitic transformation in plutonium alloys is proposed. According to this mechanism, an orientation variant of the ␣ phase is produced by a combination of a homogeneous strain and shuffling of the alternating close-packed (111) ␦ planes. It is shown that the formation of stable transformation-induced twins whose twin-plane orientations and twinshear directions do not depend on the small variations of the crystal-lattice parameters is the preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
9
0
1
Order By: Relevance
“…High resolution TEM revealed that the α′ / δ interface is composed of a terrace and ledge structure that is faceted on {111} δ , in line with the topological model discussed by Hirth et al [18]. A number of studies, beginning with Choudhry and Crocker [53], then Olson and Adler [54], and Jin et al [55] applied theories of martensite crystallography to determine the habit plane of the α′ particles in the δ matrix. Most of these studies predicted a {123} δ habit plane with 24 variants, whereas optical metallography revealed only 4 variants, possibly implying a {111} δ habit plane.…”
Section: The δ → α′ Isothermal Martensitic Transformationsupporting
confidence: 62%
“…High resolution TEM revealed that the α′ / δ interface is composed of a terrace and ledge structure that is faceted on {111} δ , in line with the topological model discussed by Hirth et al [18]. A number of studies, beginning with Choudhry and Crocker [53], then Olson and Adler [54], and Jin et al [55] applied theories of martensite crystallography to determine the habit plane of the α′ particles in the δ matrix. Most of these studies predicted a {123} δ habit plane with 24 variants, whereas optical metallography revealed only 4 variants, possibly implying a {111} δ habit plane.…”
Section: The δ → α′ Isothermal Martensitic Transformationsupporting
confidence: 62%
“…The calculations of Jin et al [22] showed that the (205) a¢ twin is the energetically preferred twin (for their variants 1 and 4). While these calculations do not show that the twist minimizes the invariant plane strain, it probably does minimize interface energy.…”
Section: Twin Relationship In A¢mentioning
confidence: 99%
“…2. La deformación que permite la obtención de las dimensiones correctas de la estructura cristalina es conocida como la deformación de Bain [16]. Fig.…”
Section: Deformación De Bainunclassified